The Political and Economic Dependence of the Press in Macao under Portuguese and Chinese Rule: Continuity and Change - Costa-Ribeiro, Nelson; Simões, José Manuel (Communication & Society, 2021)
The article analyses the media system in Macao, a special administrative region of China that transitioned from Portuguese to Chinese sovereignty in 1999, becoming one of cities in the world with the largest number of published newspapers per capita. Combining historical research with the analysis of contemporary empirical data collected through interviews with journalists working on the ground, the research demonstrates how there is a long tradition of state control that goes back to the colonial era and that has assumed different forms, ranging from outright censorship to physical intimidation of journalists and economic dependence on the government. Limitations and control strategies imposed on news reporting during the Portuguese administration continue to be practiced today by the Chinese authorities. Even so, journalists operating on the Macao media market tend to overstate the level of freedom they are given, which can be attributed to media outlets being economically dependent on the state. Nevertheless, the level of freedom attributed to the press is today higher than it had been during the colonial period with some critical voices being allowed to reach the media. This needs to be understood in the context of what has been defined as the Chinese safety valve strategy.
Number: 1
Keywords: Censorship; Journalism Practice; Media Systems; Press Freedom; Press Subsidies

Multilingual freedom of the press in Macau - Simões, José Manuel; Mayes, Lee ([RMd] RevistaMultidisciplinar, 2020)
There can be no conclusive determining regarding true press freedom in Macau, and perhaps this statement can be applied elsewhere as well. Issues of self-censorship, partisanship, or cultural loyalty exist in cities and countries around the world, and most of the time there is simply no reliable measurement to determine their impact. The Special Administrative Region (SAR) of Macau is separate and distinct from mainland China, but that does not mean that it is entirely without question regarding its freedom of the press, ethical journalistic practices, and interference by non-authorized agencies at the three languages local newspapers.
Number: 1 Publisher: NMd, Núcleo Multidisciplinar, UAlg
Keywords: autocensura; ingerência; liberdade de imprensa; partidarismo; práticas éticas

La terre des autochtones potiguara du brésil: une construction sociale et politique - Simões, José Manuel (E-Journal of Intercultural Studies, 2022)
The land of the potiguara indians of Brazil: a social and political construction The space in which the potiguaras of Brazil live is, today as in the past, the result of a longterm process, many negotiations and well-managed refuges. Paradoxically, despite their recurrent discourse invoking the ancestry of their lands of origin, the Potiguara fight and continue to fight politically for the return to the spaces where their colonial refuge took place.

A reserva territorial dos aborígenes potiguaras do Brasil: um locus simbólico - Simões, José Manuel (Revista Internacional em Língua Portuguesa, 2023)
The various volumes coordinated by Pierre Nora to pursue a history of the places of memory in France have become a multidisciplinary theoretical reference for those who, like us, seek to reconstruct the memories with which the land of the Potiguara aborigines of Brazil is organized today. In the introduction to the voluminous work that he directed for eight years, Nora explained his epistemic understanding of the notion of “places of memory”, stressing that a “lieu de mémoire” is any significant entity that, material or immaterial in nature, through a human will or the wear and tear of time, has become a symbolic element of a community's memorial heritage. The French historian also added that, since memory is the fundamental structure of this generally lengthy process, it was convenient to understand it as a phenomenon of emotions and magic that only accommodates the facts that feed it. Strictly speaking, memory is always vague, and reminiscent, stirring both general impressions and fine symbolic details. Furthermore, memory is always vulnerable to transference, repressed and imagined memories, censorship, and all kinds of projections. (Nora, 1984). In this article, we try to understand that the places of memory are also almost always what comes to us, stays, and selects the past. The reserve where they live appears as a symbolic locus to which the Potiguara aborigines cling with all their strength to preserve what remains of their past.
Keywords: aborígenes Potiguara; censuras; locus simbólico; lugares de memória; preservar o passado; reconstrução das memórias